Comparing health-issues of Russian-speaking immigrants, Germans and Russians. Issue 1 (16th March 2015) - Bachmann, Viktoria; Teigeler, Katharina; Hirsch, Oliver; Bösner, Stefan; Donner-Banzhoff, Norbert
Abstract : Purpose: – About three million Russian-speaking immigrants from the former Soviet Union live in Germany. However, little is known about their health status. The purpose of this paper is to investigate mental and physical complaints among this immigrant group through German primary care compared with native-born Germans and Russians. Design/methodology/approach: – In the context of the quantitative part of our mixed-methods study Russian-speaking immigrants, native-born Germans and Russians completed self-rating questionnaires in their native languages comprising indicators of mental and somatic health. Included were two modules of the Patient Health Questionnaire (PHQ-9, PHQ-15), and the Hamburg Self-Care Questionnaire. Findings: – No differences were found between the three groups regarding depressive and somatic symptoms. Germans had higher ratings of general health status compared to immigrants and native-born Russians and were more satisfied with their physical health than immigrants. Germans were more convinced that they can actively contribute to their health than immigrants and Russians. Germans and Russians have higher scores of self-care than immigrants. Immigrants have more subjective physical health-related complaints than non-immigrants. There are different health beliefs in the three groups which could differentially affect global well-being. Originality/value: – As minorities are double socialized in the origin and host country, a minimum of three groups have to be compared to receive a reliable statement about migration- and culture-specific differences in health related aspects. These requirements of comparative cultural psychology are satisfied by our work.